Quantitative radionuclide imaging of bone metastases - De Schepper, Stijn; Ritt, Philipp; Van den Wyngaert, Tim; Kuwert, Torsten (Quarterly Journal of Nuclear Medicine and Molecular Imaging, 2019)
By improving the localization of foci of pathological tracer uptake and offering information on their computed tomography (CT) morphology, single photon emission computed tomography (SPECT)/CT hybrid imaging has considerably improved the diagnostic accuracy of skeletal scintigraphy. SPECT/CT also has the potential to measure tracer uptake in vivo in absolute units. The present article reviews the methodology for and the potential clinical impact of quantitative skeletal scintigraphy.
CRIS-Team Scopus Importer:2019-09-27